Bispidines for Dual Imaging. Issue 51 (24th October 2014) - Stephan, Holger; Walther, Martin; Fähnemann, Silke; Ceroni, Paola; Molloy, Jennifer K.; Bergamini, Giacomo; Heisig, Fabian; Müller, Christa E.; Kraus, Werner; Comba, Peter
Abstract The efficient transformation of the hexadentate bispidinol 1 into carbamate derivatives yields functional bispidines enabling convenient functionalization for targeted imaging. The BODIPY‐substituted bispidine 3 combines a coordination site for metal ions, such as radioactive 64CuII, with a fluorescent unit. Product 3 was thoroughly characterized by standard analytical methods, single crystal X‐ray diffraction, radiolabeling, and photophysical analysis. The luminescence of ligand 3 was found to be strongly dependent on metal ion coordination: CuII quenches the BODIPY fluorescence, whereas NiII and ZnII ions do not affect it. It follows that, in imaging applications with the positron emitter 64CuII, residues of its origin from enriched 64Ni and the decay products 64NiII and 64ZnII, efficiently restore the fluorescence of the ligand. This allows for monitoring of the emitted radiation as well as the fluorescence signal. The stability of the 64CuII3 complex is investigated by transmetalation experiments with ZnII and NiII, using fluorescence and radioactivity detection, and the results confirm the high stability of 64CuII3. In addition, metal complexes of ligand 3 with the lanthanide ions TbIII, EuIII, and NdIII are shown to exhibit emission of the BODIPY ligand and the lanthanide ion, thus enabling dual emission detection.